Narrativism and Historiography - Feuereis, Eduard (Dějiny – teorie – kritika, 2011)
The topic of the article is the observation and analysis of the narrative structures of historiographic works, arising from the basic assumption that a historical text is from a certain point a view a work of prose, a work whose formal structure is poetic and thus at least partially subject to the rules of the literary production of fiction. The main theoretical framework of this work is the narrativist criticism by Hayden White, which offers instruments for the analysis of the poetical structure of a historiographic work. Besides narrative structures of the historical text, the work thematises also the role of the author (historian) – put more precisely his/her stylisations and the functions that arise from these stylisations. Thee primary sources of the thesis are Czech historical works dealing with the Baroque, re-Catholisation, and the Reformation in the Czech lands.